Bias Gender Dalam Cerita Rakyat: (Analisis Naratif pada folklore Eropa, Cinderella, dengan Cerita Rakyat Indonesia, Bawang Merah Bawang Putih) - Setiawan, Yuliyanto Budi; Fanani, Fajriannoor; Julianto, Edy Nurwahyu (Universitas Semarang, 2013)
Any interesting to compare the phenomenon of European folklore and Indonesian folklore. This study uses narrative analysis techniques. For research purposes, such as: the gender bias describes the structure presented in the story of Indonesian folklore (Bawang Merah Bawang Putih) and European folklore (Cinderella). Then, to describe the gender bias presented in the discourse structure from the story of Indonesian folklore and European folklore. Meanwhile, the results of this study can be drawn some important points encountered in both the folklore. First, the women s attitudes are passive, forgiving, not aggressive, and accept whatever ( nrimo ) is a good female figures. Second, the women s attitudes are active, ambitious, and aggressive is a bad woman figures. Third, the good woman attitudes can not changes the fate of their own, without the help of a miracle or the help of a man.